IMPLEMENTASI PEMBELAJARAN KOOPERATIF DENGAN PROBLEM POSSING TERHADP KEMAMPUAN BERPIKIR ANALOGI MATEMATIS SISWA - Prahesti Tirta Safitri; Kus Andini Purbaningrum (JPPM (Jurnal Penelitian dan Pembelajaran Matematika), 2019)
The ability of mathematical reasoning is a very important ability possessed by students in solving math problems, because this skill is a withdrawl basics in conclusion. One of the most basic reasoning ability is the mathematical analogy thinking. However this ability is the fact on the school is still low. So the need for an effort to develop it. One solution is with the cooperative learning with problem possing. Based on these problems, then the purpose of this study was to examine the influence and difference mathematical analogy thinking ability of students. This research design using Nonequivalent Control Group Design, which consists of classroom experiments, namely the use of cooperative learning with problem possing approach and class with cooperative learning. Based on the results of the analysis of data obtained as a result of that achievement of mathematical analogy thinking ability of students who get a cooperative learning with problem possing better than students who get only a learning cooperative. Keywords: Cooperative Learning, Problem Possing,  Mathematical Analogy Thinking